Empowering women in the digital age: can digital financial services fulfil the promise of financial autonomy and gender equality in the attainment of Sustainable Development Goal 5? - Mohsin Showkat; Razia Nagina; Usha Nori; Muzamil Ahmad Baba; Mohd Asif Shah (Cogent Economics & Finance, 2024)
Digital financial services play a crucial role in breaking down traditional barriers to financial access, promoting greater financial inclusion, and providing marginalized groups with equal access. These services offer innovative strategies designed to address the unique financial barriers and empower women to achieve financial access and independence. This study aims to examine the influence of the adoption of digital financial services on enhancing women's financial independence. This study examines the responses of 426 women in North India using Partial Least Squares Structural Equation Modelling (PLS-SEM) as its research approach. This study also employs the PLS Predict technique to evaluate the ability of the model to predict women's financial autonomy. The findings demonstrate a significant and favourable relationship between the utilization of digital financial services and the improvement of women's ability to make financial decisions. This study contributes to the discussion on promoting gender equality and economic empowerment, aligning with United Nations Sustainable Development Goal 5; showcasing the potential of information and communication technology (ICT) in advancing women's economic and social empowerment. The results offer vital perspectives for policymakers, financial service providers, and development agencies, emphasizing the substantial influence of digital financial services in promoting gender parity and enhancing women's socio-economic circumstances.
Keywords: 330; Digital financial services; female financial independence; empower-ment; gender equality; SDG 5